Enhancing the durability of concrete made of concrete recyclate by additives and admixtures - Stehlík, Michal (Journal of Civil Engineering and Management, 2014)
The aim of this research is to find an optimum combination of silicate admixtures and epoxy dispersion additives which would positively influence the durability and mechanical properties of concretes made of concrete recyclate. The durability of concrete is dependent on its cover layer permeability and also on the overall permeability of concrete recyclate. The cover layer permeability was evaluated by means of three methods, namely the air permeability method TPT and two methods of measuring water permeability, GWT and ISAT. Fine silicate admixtures and dispersion additives influence the air and water permeability of concrete made of concrete recyclate in different ways. The dose of 10% of microsilica or 30% of slag or fly ash decreases the air permeability of concrete. Water permeability, on the other hand, is decreased by adding a dose of 12% of pure epoxy dispersion. As regards improving the mechanical properties of concrete made of concrete recyclate, it seems to be promising to use a combination of 30% of slag admixture or 10% of microsilica admixture with 12% of epoxy dispersion additive. However, the price of admixtures and additives is relatively high. That is why additive enhanced concretes made of concrete recyclate are intended for special purposes.